(untitled) (The Informal: South Asian Journal of Human Rights and Social Justice, 2025)
The judiciary, as the constitutional custodian of justice, is mandated to adjudicate with the Constitution, statutory provisions, and universally recognized principles of justice. Over the years, Nepal’s judiciary has significantly played a transformative role in shifting the legal narrative on child marriage —from a culturally accepted, socially normalized, and legally ambiguous practice to a serious violation of fundamental rights. This doctrinal shift is evident in key jurisprudences, where the Court has progressively adopted a purposive, rights-based adjudicatory approach that centers on the victim and child, grounded in the principle of the “best interests of the child” and departing from rigid statutory formalism. The shift in the courts reflect a broader interpretive shift How to Cite this Article away from rigid legal formalism toward a more survivor-informed, context-sensitive adjudicatory framework. A defining milestone in this evolution is the Supreme Court’s ruling in Government of Nepal v. Santosh Kumar Yadav, which reaffirmed core constitutional values—dignity, equality, and protection from exploitation—while operationalizing international child rights obligations. This article undertakes a doctrinal analysis of the decision, examining the Court’s interpretive reasoning, its alignment with global jurisprudence, its adherence to constitutional and statutory mandates, and its application of international legal standards. Despite these advances and clear adjudicatory guidance, inconsistencies across various courts reveal persistent lack of doctrinal clarity and shared understanding within the judiciary – ranging from limited institutionalization of child rights-based practices to prevailing reliance on rigid, traditionalist interpretation of law that disregards liberal approaches grounded in established precedents. This article, therefore, underscores the need for doctrinal consistency, institutional alignment, and enhanced judicial education to ensure a coherent, uniform, and child-centered approach to justice. By tracing this evolving jurisprudential landscape, the article highlights both the normative progress made and the structural reforms still required to realize Nepal’s constitutional mandates and international commitments to protect children’s rights.